Independent Learning in the Digital Era, The Relationship of Digital Literacy with Self-Directed Learning in High School Students (Departement of Psychology, Faculty of Education, Universitas Negeri Semarang, 2023)
Education has been shifted to a digital environment nowadays. Students must adapt to theimplementation of distance learning. This online learning requires the activeness of students,especially to be independent in learning—self-directed learning. However, with many learningresources on the internet, digital literacy is also needed so that students can carry out their self-directed learning better. This study aims to determine whether there is a relationship between digitalliteracy and self-directed learning in high school students. This research method is quantitative witha correlational design. The sample for this study used a proportionate stratified random samplingtechnique and obtained as many as 259 1st and 2nd year students from SMAN 6 Semarang. Themeasuring instruments used are the digital literacy scale and the self-directed learning scale, withCronbach's Alpha reliability scores of 0.827 and 0.851, respectively. The results of hypothesis testingare the acceptance of the working hypothesis, so it can be concluded that there is a relationshipbetween digital literacy and self-directed learning. The correlation coefficient obtained is 0.217. Inaddition, descriptively, it is known that the subject's self-directed learning condition is in the mediumcategory and the subject's digital literacy condition is also in the moderate category.